The Sheiks of Abi Al-Qasim Al-Jurjani and His Students through His Book History of Jurjan and the Sources Mentioned in His Translation - Zaidan Alobaidi, Reem Mahmood; Hussen Alzaidi, Maha Abdulrahman (Journal of Tikrit University for Humanities, 2024)
The research studies the sheikhs of the Imam, the Hafiz, the Muhaddith, the Muhaddith Abu al-Qasim al-Jurjani, as well as his students, These sheikhs were from Gorgan itself, which is his hometown, as he took him and heard from many sheikhs of other cities, Such as Isfahan, Nishapur, Ahwaz, Baghdad and others, where he learned hadith, jurisprudence and principles from them, He stated their names in his book, The History of Jurgan, when he transmitted their stories and some of their news from them. Some of them were translated and it was mentioned that he heard from them expressing that with words indicating hearing and permission, such as: I heard, tell me, tell us, and other expressions and other formulas. Just like Abu Al-Qasim Al-Jurjani took from a large number of sheikhs, a number of those who sought knowledge in his time also learned from him, and this is evidence of his rank and high status.